Follow‐up on the characterization of peptidic markers in hair and fur for the identification of common North American species. (31st July 2017) - Solazzo, Caroline
Abstract : Rationale: Species identification of hair is routinely done by microscopic analysis. Following previous studies that used protein analysis to characterize species markers in hair and wool, the present work aims at covering a larger number of species and to ultimately offer a method for rapid hair identification in forensics and archaeology. Methods: Hair is mostly made of alpha‐keratins; these proteins have only been sequenced in a handful of species and most animal families are under‐represented. Using a methodology developed for the characterization of peptidic markers in tissues such as bone (peptide mass fingerprinting or PMF) and commonly applied on collagen, hair from common North American fur‐bearing species was analyzed by MALDI‐TOF‐MS to obtain peptidic profiles. Results: Alpha‐keratin peptides that are typically dominant on peptide mass profiles of hair were chosen as markers. Matching peaks were identified for each species tested and compared to known sequences from related organisms whenever possible. The markers were used to create a flowchart to narrow down identification to the family level. Conclusions: The methodology was developed on a limited numbers of markers chosen for their variability and reliability on the peptide mass fingerprint. In the absence of genetic sequences, this strategy is a quick way to compare species from a common geographic origin. The work presented here was focused on North American species but could be applied to other animal families.